Factores demográficos maternos y estado nutricional en preescolares - Lujan Revilla, Carolina del Milagros (2019)
The present study is a quantitative, descriptive-correlational type, carry out in Trujillo, whose purpose was to determine the relationship between the maternal demographic factors: age, educational level, marital status, economic income and occupation; and the nutritional status of the preschool of I.E.I N° 1582 “Mis Angelitos” in Víctor Larco Herrera-Trujillo, 2018. The sample consisted of 120 mothers and their respective children who met the inclusion criteria. Data collection was carried out through the application of two instruments: a questionnaire to determine the maternal demographic factors and a scorecard for the nutritional status of the child under 5 years of the MINSA. The information was processed and analyzed using the "chi square" statistical test, concluding that, of the maternal demographic factors, 57.5 percent are young adult mothers, 62.5 percent have a basic education degree; 75.8 percent have a partner; 68.3 percent have a low economic income; 52.5 percent are unemployed. According to the height-for-age indicator, 98.3 percent of children have a normal nutritional status and 1.7 percent have short stature; according to the weight-for-height indicator, 75 percent have a normal nutritional status and 25 percent between overweight and obesity; According to the weight-for-age indicator, 90.8 percent have a normal nutritional status and 9.2 percent are overweight. There is a significant relationship in maternal demographic factors: age and marital status with nutritional status.